A Type II Split Cord Malformation in an Adult Patient: An Operative Case Report. Issue 2 (8th December 2020) - Oh, Taemin; Avalos, Lauro Nathaniel; Burke, John Frederick; Mummaneni, Nikhil; Safaee, Michael; Gupta, Nalin; Clark, Aaron J
Abstract: BACKGROUND AND IMPORTANCE: Split cord malformations (SCMs) are rare conditions in which the spinal cord is split into two hemicords within either a single thecal sac or two separate thecal sacs. The hemicords are typically split by a bony or fibrous structure. We present an adult patient who presented with a type II SCM with tethered cord. This is the first case of such a presentation with an accompanying intraoperative video. Unusual features of the case were the presence of an incomplete fibrous septum and lack of a discrete filum terminale. CLINICAL PRESENTATION: A 50-yr-old woman presented with back pain, radiculopathy, urinary urgency, and episodic fecal incontinence. Her exam was notable for weakness of the right extensor hallicus longus. Imaging showed an SCM extending from L3 to S1, a fibrous septum located at L4-5, and a low-lying conus at S4. She was treated with a decompressive L3-S4 laminectomy and disconnection of all the dural attachment points. She required lumbar drain placement postoperatively and reoperation for wound dehiscence and persistent pseudomeningocele. At the time of last follow-up, she was neurologically intact with improvement in bowel/bladder function. CONCLUSION: SCM is an uncommon presentation in adults and is often accompanied by findings of skin stigmata, tethered cord, and other central nervous system/skeletal anomalies. Obtaining full multimodal imaging is critical to understanding subtle anatomic variations that can pose operative challenges. We report the treatment of an adult patient with type II SCM, and provide an intraoperative video demonstrating the removal of an incomplete midline fibrous septum.